2021
DOI: 10.3856/vol49-issue1-fulltext-2564
|View full text |Cite
|
Sign up to set email alerts
|

Total or partial replacement of fishmeal with soybean meal in the diet of the Pacific fat sleeper Dormitator latifrons juveniles

Abstract: Groups of Dormitator latifrons in triplicate (4.1 ± 2.0 g and 6.2 ± 1.0 cm) were fed experimental diets containing four levels of substitution of fishmeal (FM) by soybean meal (SM) (0, 40, 70, and 100%, respectively). The diets were formulated to be isoproteic (35% crude protein) and isolipidic (8.0% crude lipids). The effect of each treatment on growth was evaluated and its implications on the cost of feeding. After 60 days of feeding, there were no significant differences in the fish's proximate composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
2
2
0
2
Order By: Relevance
“…In the present study, replacing 50% of FM with SM did not impair the growth performance of pikeperch. This result is consistent with a study in which FM was replaced with up to 100% SM in the diet of an omnivorous fish, Pacific fat sleeper (Dormitator latifrons), and showed adequate growth without effects on body composition and survival (Badillo-Zapata et al, 2021). Replacement of FM up to 70% with crude protein from toasted soybean meal also did not compromise growth of carnivorous blue catfish, Ictalurus furcatus (Webster et al, 1992).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, replacing 50% of FM with SM did not impair the growth performance of pikeperch. This result is consistent with a study in which FM was replaced with up to 100% SM in the diet of an omnivorous fish, Pacific fat sleeper (Dormitator latifrons), and showed adequate growth without effects on body composition and survival (Badillo-Zapata et al, 2021). Replacement of FM up to 70% with crude protein from toasted soybean meal also did not compromise growth of carnivorous blue catfish, Ictalurus furcatus (Webster et al, 1992).…”
Section: Discussionsupporting
confidence: 90%
“…Despite considerable success in partially or completely replacing fishmeal with soybean meal in fish feed (Al-Kenawy et al, 2008;Ajani et al, 2016;Rahimnejad et al, 2021;Badillo-Zapata et al, 2021), the problems with palatability, digestion, nutrient utilization, and antinutritional factors (ANFs) such as b-conglycinin, protease inhibitors, and oligosaccharides continue to limit the substitution of SM for FM in carnivorous fish diets (Mambrini et al, 1999;Papatryphon and Soares, 2001;Peres et al, 2003;Zhou et al, 2005). It is well established that high levels of SM in the diet of carnivorous fish often have negative impacts on growth rate, protein and lipid metabolism, and health status (Refstie et al, 1998;Mambrini et al, 1999;Chou et al, 2004;Tomas et al, 2005;Zhou et al, 2005;Choi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For a native species of Mexico, Dormitator latifrons, the increase in the percentage of soybean meal in the diet reduced the feed cost and making it possible to completely replace fishmeal, providing adequate performance combined with cost reduction in a recirculation system (Badillo-Zapata et al, 2021). This data corroborate our study, as we also found a reduction in feed costs without interfering with fish growth performance.…”
supporting
confidence: 89%
“…That study concluded that a diet containing 30% proteins and 8% lipids was enough for ensuring a good development of these fish (Badillo- . Recently, Badillo- Zapata et al (2021) experimented with partial and total substitution of fishmeal by soybean meal in juveniles feed; the results did not show negative effects in growth and apparent digestibility, suggesting the species absorbs an adequate amount of nutrients from vegetable sources.…”
Section: Eating Habits and Nutritionmentioning
confidence: 98%